Analysis of local government supervision in surface mining: The case of Bulukumba Regency - Sam, Aldiani Fitriayu; Arifin, Indar; Syamsu, Suhardiman (Department of Government Science, 2024)
Supervision is the prevention or correction of errors, irregularities, discrepancies, and misappropriations that are not in accordance with the objectives of the predetermined authority. This study aims to determine how the form of local government supervision in supervising rock quarry mines in Bontotiro District, Bukukumba Regency. This study used a qualitative descriptive approach, and the data collection used observation, interviews, and documentation. Data was analyzed through the stages of data collection, data reduction, data presentation, and conclusions. This study shows how local government supervision of rock quarry mines in the study area is seen from two forms of supervision. First, preventive supervision was carried out before the implementation of mining activities through the supervision of exploration Mining Business Permits (IUP) for exploration implementation and Mining Business Permits (IUP) for production operations. Second, repressive supervision carried out during the implementation of mining activities refers to the supervision of Rock Excavation Production Operation Activities.